Surgery with Radical Intent: Is There an Indication for G3 Neuroendocrine Neoplasms? - Merola, Elettra; Rinke, Anja; Partelli, Stefano; Gress, Thomas M.; Andreasi, Valentina; Kollár, Attila; Perren, Aurel; Christ, Emanuel; Panzuto, Francesco; Pascher, Andreas; Jann, Henning; Arsenic, Ruza; et al. (Annals of surgical oncology, 2020)
Background While platinum-based chemotherapy represents the standard treatment for advanced grade 3 (G3) neuroendocrine neoplasms (NENs) according to the European Neuroendocrine Tumor Society guidelines, the role of radical-intended surgery in these patients, as well as the use of adjuvant chemotherapy, are still controversial. The aim of the present work is to describe, in a retrospective series of gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) G3, the overall survival (OS) rate and risk factors for death after radical surgery. Secondary aims are the description of median recurrence-free survival (RFS) and of the role of adjuvant chemotherapy. Patients and Methods Multicenter analysis of a series of stage I–III GEP-NEN G3 patients receiving radical surgery (R0/R1) with/without adjuvant chemotherapy was performed. Results Sixty patients from eight neuroendocrine tumor (NET) referral centers, with median follow-up of 23 months (5–187 months) were evaluated. While 28.6% of cases had NET G3, 71.4% had neuroendocrine carcinoma G3 (NEC G3). The 2-year OS rate after radical surgery was 64.5%, with a statistically significant difference in terms of Ki67 threshold (cut-off 55%, P = 0.03) and tumor differentiation (NEC G3 vs. NET G3, P = 0.03). Median RFS after radical surgery was 14 months, and 2-year RFS rate was 44.9%. Use of adjuvant chemotherapy provided no benefit in terms of either OS or RFS in this series. Conclusions Surgery with radical intent might represent a valid option for GEP-NEN G3 patients with locoregional disease, especially with Ki67 value ≤ 55%.